Design and implementation of a novel patient-centered empowerment approach for pain optimisation in children undergoing major surgery. Issue 3 (19th July 2022) - Chidambaran, Vidya; Simpson, Blair; Brower, Laura; Hanke, Rachel; Mecoli, Marc; Lane, Blake; Williams, Sara; McKenna, Emily; Bates, Christina; Kraemer, Aimee; Sturm, Peter; Brown, Rebeccah; et al.
Abstract : Background: Paediatric surgery is a stressful experience for patients and caregivers. While standardised protocols are the norm, patient-centred approaches are needed to empower patients/caregivers for an optimal perioperative pain experience. To address this gap, we employed a patient-centred approach using design thinking (DT) methodology to develop insights, map processes, identify opportunities and design solutions for individualised empowerment tools. Methods: In consultation with DT experts, a multidisciplinary team of stakeholders (healthcare providers, patients who underwent pectus excavatum/scoliosis surgery and their caregivers), were invited to participate in surveys, interviews and focus groups. The project was conducted in two sequential stages each over 24 weeks—involving 7 families in stage 1 and 16 patients/17 caregivers in stage 2. Each stage consisted of three phases: design research (focus groups with key stakeholders to review and apply collective learnings, map processes, stressors, identify influencing factors and opportunities), concept ideation (benchmarking and co-creation of new solutions) and concept refinement. Results: In stage 1, mapping of stress/anxiety peaks identified target intervention times. We identified positive and negative influencers as well as the need for consistent messaging from the healthcare team in our design research. Current educational tools were benchmarked, parent-child engagement dyads determined and healthcare-based technology-based solutions conceived. The 'hero's journey' concept which has been applied to other illness paradigms for motivation successfully the was adapted to describe surgery as a transformative experience. In stage 2, patient and caregiver expectations, distinct personas and responses to perioperative experience were categorised. Educational tools and an empowerment tool kit based on sensorial, thinking, relaxation and activity themes, tailored to parent/child categories were conceptualised. Conclusion: DT methodology provided novel family centred insights, enabling design of tailored empowerment toolkits to optimise perioperative experience. Adapting the hero's journey call to adventure may motivate and build resilience among children undergoing surgery.